Consequences of age-related cognitive declines.[article]. - Salthouse, Timothy
Adult age differences in a variety of cognitive abilities are well documented, and many of those abilities have been found to be related to success in the workplace and in everyday life. However, increased age is seldom associated wiht lower levels of real-world functioning, and the reasons for this lab-life discrepancy are not well understood. This article bfrielfy reviews research concerned within relations of age, to cognition, relations of cognition to successful functioning outside the laboratory, and relations of age to measures of work performance and achievement. The final section discusses several possible explanations for why theere are often little or no consequences of age-related cocgnitive declines in everyday functioning. - (from the author)
Keywords: Aging; Cognitive aging; Cognitive functioning; Job performance; Accommodations; Typical versus maximal performance